Preliminary study of solid waste treatment of Padang Beach tourism area - Aziz, Rizki; Adfuza, Gloria Poppy; Arbi, Yaumal (Universitas Negeri Padang, 2021)
A preliminary study of the solid waste treatment in the Padang Beach tourist area was done in order to analyze solid waste generation, composition, and the potency of recycling, and to recommend the appropriate treatment system applied to the tourist area. The study revealed that daily waste generated 18.648 L, the components of the waste dominated by food waste 84.215%, plastic 9.254%, paper 2.087%, and non-metal ferrous 1.945%. The potency of recycling of the waste was food waste 91.732%, plastic 88.074%, metals 78.947% and glass 75.758%. This study it is recommends that waste that has an economic value such as plastic, paper, and metal should be collected and sold to a third party, biodegradable waste such as food waste and yard waste should be composted, while other waste that has potency to produce handy craft such as seashell, coconut shell, and sachet packaging should be collected and processed, all treatment activities can be done at the recycling centre that located in the tourist area.